2018
DOI: 10.3847/1538-4357/aab202
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Study of Variable Gamma-Ray Pulsar PSR J2021+4026

Abstract: PSRJ2021+4026 showed a sudden decrease in the gamma-ray emission at the glitch that occurred around 2011 October 16, and a relaxation of the flux to the pre-glitch state at around 2014 December. We report X-ray analysis results of the data observed by XMM-Newton on 2015 December 20 in the post-relaxation state. To examine any change in the X-ray emission, we compare the properties of the pulse profiles and spectra at the low gamma-ray flux state and at the post-relaxation state. The phase-averaged spectra for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…This result, not found in previous works, implies that the mode change also affects the Xray emission, suggesting a modification in the magnetospheric regions connecting the dipole field with the inner components close to stellar surface. We have also reproduced the results of the previous X-ray timing analyses of the two XMM-Newton data sets by Lin et al (2013) and by Wang et al (2018), respectively. Given the implications of this result, we discuss all the validations that we performed to rule out possible systematic errors in our analysis.…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…This result, not found in previous works, implies that the mode change also affects the Xray emission, suggesting a modification in the magnetospheric regions connecting the dipole field with the inner components close to stellar surface. We have also reproduced the results of the previous X-ray timing analyses of the two XMM-Newton data sets by Lin et al (2013) and by Wang et al (2018), respectively. Given the implications of this result, we discuss all the validations that we performed to rule out possible systematic errors in our analysis.…”
Section: Introductionsupporting
confidence: 87%
“…Following this recovery, we triggered a target of opportunity (ToO) observation with XMM-Newton (PI: Razzano, Obs ID: 118 0763850101). Based on these data, Wang et al (2018) found no significant change in either the pulsar X-ray emission or in the relative phase shift between the γ-ray and X-ray pulse profiles taken around April 2012 (MJD 56027 (i.e. after the flux drop) and November 2015 (MJD 57376 (i.e.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is expected that if the abrupt state change of PSR J2021+4026 is caused by the twisting of the magnetosphere, the emission from the heated footprint contributes to the observed X-ray emission in a HSD state. In the previous studies of the X-ray emission from PSR J2021+4026 (Lin et al 2013;Wang et al 2018), there is no apparent difference between the X-ray emission properties in the HSD and LSD states. It is therefore that the twisted magnetosphere will not be the reason of the state change of PSR J2021+4026.…”
Section: Discussionmentioning
confidence: 81%